1998
DOI: 10.1002/(sici)1097-4679(199812)54:8<1137::aid-jclp12>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the treatment climate in psychiatric and substance abuse programs

Abstract: This study examines how key aspects of the treatment climate are related to program differences in the aggregate behaviors of patients residing in 89 psychiatric or substance abuse facilities. More active support, personal expression, and practical orientation were related to better patient functioning, more patient activity in the facility and in the community, and more use by patients of the program's health-treatment services and social-recreational activities. These results held for both patients' and staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
1
29
0
2
Order By: Relevance
“…Specifically, younger age (Kruzich, 1985;Nagy, Fisher, & Tessler, 1988), higher psychosocial functioning (Kruzich, 1985), greater social competence (Kennedy, 1989), and less psychopathology (Segal & Everett-Dille, 1980;Timko & Moos, 1998) have been associated with higher levels of physical integration.…”
Section: Determinants Of Community Integrationmentioning
confidence: 99%
“…Specifically, younger age (Kruzich, 1985;Nagy, Fisher, & Tessler, 1988), higher psychosocial functioning (Kruzich, 1985), greater social competence (Kennedy, 1989), and less psychopathology (Segal & Everett-Dille, 1980;Timko & Moos, 1998) have been associated with higher levels of physical integration.…”
Section: Determinants Of Community Integrationmentioning
confidence: 99%
“…Self-help groups, often based on the 12-step philosophy, have played an important role in furthering the recovery of persons who have addictive disorders as well as persons with mental illness (16)(17)(18)(19)(20)(21)(22). However, some members of 12-step groups who have dual diagnoses report receiving misguided advice about psychiatric illness and the use of psychiatric medications, which are seen as "drugs" (23), although this is not the official view of Alcoholics Anonymous or Narcotics Anonymous (24,25).…”
mentioning
confidence: 99%
“…Several studies have suggested that staff beliefs about treatment are a key factor in determining their acceptance of new treatment approaches, including the adoption of evidence-based practices (Amodeo, 2000;Humphreys, Noke, & Moos, 1996;Ball et al, 2002;Forman, Bovasso, & Woody, 2001;Forman et al, 2002). Climate has also been used to refer to the "treatment milieu" (Timko & Moos, 1998) or "treatment orientation" (Lee, Reif, Ritter, Levine, & Horgan, 2001;Moos, King, Burnett, & Andrassy, 1997;.…”
Section: Organizational Characteristicsmentioning
confidence: 99%